2019
DOI: 10.1080/15376494.2018.1519619
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of impact on wood-based sandwich structures

Abstract: The impact behavior of innovative wood based sandwich structures with plywood core and skins made either of aluminum or of fiber reinforced polymer (carbon, glass, or flax composite skins) was investigated numerically. The wood based sandwich structures were subjected to low-velocity/low-energy impacts. An explicit nonlinear numerical model based on volume elements with a cohesive layer was developed. A plastic wood law already implemented in LS-DYNA was used in association with composite type damage criteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In addition, to better understand the crush behaviour of wood tubes, advanced modelling is necessary. A very limited number of papers have dealt with the subject [17] so far and a research effort has to be made to develop material damage models for wood plies, together with efficient modelling strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, to better understand the crush behaviour of wood tubes, advanced modelling is necessary. A very limited number of papers have dealt with the subject [17] so far and a research effort has to be made to develop material damage models for wood plies, together with efficient modelling strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The force-displacement curve showed that the dynamic performance of poplar was slightly better than its static performance in the longitudinal or tangential direction (Plateau force, Energy Absorbed (EA) or Specific Energy Absorbed (SEA)). There is now renewed interest in these materials and the issue [15][16][17][18]. Some very interesting studies have also been conducted on the dynamic behaviour of coconut woods [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with simple wood, plywood structures have much better physical properties, due to the material's better in-plane behavior. In order to develop a new structure and to compare configurations, we used two different plywood cores with four different skins [32][33][34][35]: two different configurations of plywood, named "A" and "B" and composed of different plies obtained from poplar and okoume wood that were bonded together using Melamine Urea Formaldehyde (MUF) resin. The stacking sequences of okoume and poplar plies are given in Table . 1.…”
Section: Sandwich Manufacturingmentioning
confidence: 99%
“…The authors of this paper have recently studied the manufacturing and the static behavior of sandwiches made with plywood core and different skins made of aluminum, glass, carbon and flax fiber laminates [32], and their low velocity, low energy impact response [33]. A first attempt to model the impact damage has been proposed [34] and the present paper focuses on compression and compression after impact (CAI) tests performed on the nine types of wood-based sandwich structures studied in [32][33][34]. Materials used in this study will be recalled briefly in the form of some impact results.…”
Section: Introductionmentioning
confidence: 99%